Why Do Consumers Use Ride-Hailing? Evidence from China and Indonesia - Gatot Gunarso (Binus Business Review, 2023)
Consumers’ attitudes and preferences in developing countries differ from those in developed countries. The research compared the motivation to use ride-hailing in developing and developed countries to understand consumers better. The research applied a qualitative survey with 52 drivers, followed by a quantitative survey with 741 passengers. It was finalized by one quantitative survey of 818 respondents to answer the research questions. The passengers in both quantitative surveys were from Indonesia and China who were Chinese, Indonesian, and Expatriates in China. Indicators in Partial Least Square-Structural Equation Modelling (PLS-SEM) were used to capture ride-hailing phenomena closer to actual business situations and made more robust measurements for future testing of consumers’ decisions in sharing economy setting. The results show that the habit factor influences the decision to use ride-hailing among Indonesian, Chinese, and Expatriate respondents. Meanwhile, the financial factor only influences Indonesian respondents. Safety factor affects Expatriate respondents, and utility and convenience factors influence the decision of Chinese respondents. Innovation and social factors are significant when the significance level is reduced to the exploratory level. In conclusion, managers of sharing economy companies in developing and developed countries can use Importance-Performance Mapping Analysis (IPMA) result in the research to identify important but weak factors that can be improved.